Optic Neuritis in the Era of NMOSD and MOGAD: A Survey of Practice Patterns in Singapore. Issue 2 (March 2022) - Foo, Reuben; Yau, Christine; Singhal, Shweta; Tow, Sharon; Loo, Jing-Liang; Tan, Kevin; Milea, Dan
Abstract: Purpose: The Optic Neuritis Treatment Trial was a landmark study with implications worldwide. In the advent of antibody testing for neuromyelitis optica spectrum disease (NMOSD) and myelin oligodendrocyte glycoprotein antibody-associated disease (MOGAD), emerging concepts, such as routine antibody testing and management, remain controversial, resulting mostly from studies in White populations. We evaluate the practice patterns of optic neuritis investigation and management by neuro-ophthalmologists and neurologists in Singapore. Design: 21-question online survey consisting of 4 clinical vignettes. Methods: The survey was sent to all Singapore Medical Council– registered ophthalmologists and neurologists who regularly manage patients with optic neuritis. Results: Forty-two recipients (17 formally trained neuro-ophthalmol-ogists [100% response rate] and 25 neurologists) responded. Participants opted for routine testing of anti–aquaporin-4 antibodies (88.1% in mild optic neuritis and 97.6% in severe optic neuritis). Anti-MOG antibodies were frequently obtained (76.2% in mild and 88.1% in severe optic neuritis). Plasmapheresis was rapidly initiated (85.7%) in cases of nonresponse to intravenous steroids, even before obtaining anti–aquaporin-4 or anti-MOG serology results. In both NMOSD and MOGAD, oral mycophenolate mofetil was the preferred option if chronic immunosuppression was necessary. Steroids were given for a longer duration and tapered more gradually than in idiopathic optic neuritis cases. Conclusions: Serological testing for NMOSD and MOGAD is considered as a routine procedure in cases of optic neuritis in Singapore, possibly due to local epidemiological features of these conditions. Chronic oral immunosuppression is preferred for the long term, but further research is necessary to establish the efficacy and cost-effectiveness of these practices.